ANALISIS AUDIO AMBISONIC DALAM MENENTUKAN ARAH BUNYI SEBAGAI RANCANGAN PEMBUATAN AUDIO FILM UNTUK DISABILITAS NETRA - Surya, Ibrahim Adi; Della Dwinanti Sumpena; Bowo Andrean (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
ABSTRACT Ambisonic audio is a recording and sound playback technique that can represent the direction and distance of sound sources in three-dimensional space. Ambisonic audio can be used to create audio for films that provide an immersive experience for the audience, especially for individuals with visual impairments who rely on spatial information from sound. This research aims to analyze Ambisonic audio using DAW Studio One and the Waves NX360 Ambisonic Audio plugin to determine sound direction as an initial design for creating audio for visually impaired individuals as an entertainment medium. Sound direction is an advantage of Ambisonic audio technology that needs to be analyzed because it covers a 360-degree or three-dimensional direction. This research uses an experimental method by creating audio samples using different Ambisonic technologies in terms of sound source direction and distance, and then testing their effects on spatial perception and on visually impaired listeners. Keywords: Ambisonic, sound direction, visual impairment, audio film